Sensory neuron-derived eph regulates glomerular arbors and modulatory function of a central serotonergic neuron - Singh, Ajeet Pratap; Evers, Jan-Felix (PLoS Genetics, 2013)
Author Summary Serotonin, a major neuromodulatory transmitter, regulates diverse behaviours. Serotonergic dysfunction is implicated in various neuropsychological disorders, such as anxiety and depression, as well as in neurodegenerative disorders. In the central nervous systems, across taxa, serotonergic neurons are often small in number but connect to and act upon multiple brain circuits through their wide-field arborization pattern. We set out to decipher mechanisms by which wide-field serotonergic neurons differentially innervate their target-field to modulate behavior in a context-dependent manner. We took advantage of the sophisticated antennal lobe circuitry, the primary olfactory centre in the adult fruitfly Drosophila melanogaster. Olfactory sensory neurons and projection neurons connect in a partner-specific manner to create glomerular units in the antennal lobe for processing the sense of smell. Our analysis at a single-cell resolution reveals that a wide-field serotonergic neuron connects to all the glomeruli in the antennal lobe but exhibits the glomerular-specific differences in its innervation pattern. Our key finding is that Eph from sensory neurons regulates the glomerular-specific innervation pattern of the central serotonergic neuron, which in turn is essential for modulation of odor-guided behaviours in an odor-specific manner.